The operational performance of physical education in primary schools at Shanxi Province - Zhang, Peng; Na Srito, Pavinee (วารสารนวัตกรรมการศึกษาและการวิจัย, 2024)
This research article aims to: 1) analyst the relationship between the dimensions of social interaction, absorptive capacity, cognitive trust, shared vision and operational performances of physical education, 2) analyst shared vision play mediating impact between social interaction, absorptive capacity, and cognitive trust on operational performances of physical education. In order to achieve this objective, the researcher has collected data from 387 core physical education teachers from 36 primary and junior high schools of various types in Shanxi were randomly selected as respondents using a convenience sampling method. The data was collected by administering a carefully designed questionnaire. When the analysis techniques were SPSS, and SEM by AMOS and applied to the collected data. Research found that: 1) Social interaction positively influences shared vision absorptive capacity. Cognitive trust positively influences shared vision. Absorptive capacity positively influences shared vision. And Shared vision positively influences the operational performance of physical education, 2) Shared vision play a mediating impact between social interaction, Absorptive capacity, and cognitive trust on operational performances of physical education.